Efavirenz and ritonavir-boosted lopinavir use exhibited elevated markers of atherosclerosis across age groups in people living with HIV in Ethiopia. Issue 13 (6th September 2016) - Gleason, Rudolph L.; Caulk, Alexander W.; Seifu, Daniel; Rosebush, Julia C.; Shapiro, Alyssa M.; Schwartz, Matthew H.; Eckard, Allison Ross; Amogne, Wondwossen; Abebe, Workeabeba
Abstract: Background: HIV patients on highly-active antiretroviral therapy (HAART) have shown elevated incidence of dyslipidemia, lipodystrophy, and markers of cardiovascular disease. Evidence is beginning to emerge that implicates efavirenz (EFV) as a potential mediator of early on-set cardiovascular disease. Methods: Pediatric and adult HIV-infected HAART-naïve, EFV-treated, nevirapine (NVP)-treated, and ritonavir-boosted lopinavir (LPV/r)-treated subjects were recruited from Black Lion Hospital in Addis Ababa, Ethiopia. Pulse wave velocity (PWV), carotid intima-media thickness (cIMT), carotid arterial stiffness, brachial artery flow-mediated dilation (FMD), body mass index, waist-to-hip circumference ratio, and skinfold thickness were measured. CD4+ cell count, fasting glucose, lipoprotein profiles and triglycerides were also determined. Results were segmented into pediatric (6–17 years of age), young adults (25–39 years old) and older adults (40–60 years old). Results: PWV was generally elevated in EFV- and LPV/r-treated subjects compared to NVP-treated subjects across age groups. cIMT was elevated in EFV- and LPV/r-treated compared to NVP-treated older adults and in EFV-treated compared to HAART-naïve older adults. FMD was impaired in EFV- and LPV/r-treated compared to HAART-naïve younger adults, in EFV-treated compared to NVP-treated young and older adults, and in LPV/r-treated compared to NVP-treated older adults. Differences in lipoprotein profiles and skinfold thickness with HAART regimen were observed in pediatric and young adults, but less so in older adults. Conclusions: Whereas LPV/r and other protease inhibitors have long been recognized as mediators of HIV/HAART-associated atherosclerosis, this report supports the emerging evidence that EFV may also mediate cardiovascular disease in people living with HIV on HAART.